Back Cover: Preparation, Structural Determination, and Characterization of Electronic Properties of [5, 6]‐ and [6, 6]‐Carbosilylated Sc3N@Ih‐C80 (Chem. Asian J. 12/2017). Issue 12 (5th June 2017) - Kako, Masahiro; Sugiura, Takeshi; Miyabe, Kyosuke; Yasui, Masanori; Yamada, Michio; Maeda, Yutaka; Guo, Jing‐Dong; Nagase, Shigeru; Akasaka, Takeshi
Abstract : Derivatization with silicon : Endohedral metallofullerenes (EMFs) have been attracting much attention because of their unique electronic structures, based on encapsulated metal atoms and metallic clusters. However, examples of synthetic methods for the functionalization of EMFs have been rather sparse compared with those for empty fullerenes. Herein, the photoreaction of Sc3 N@ Ih ‐C80 with a silirane was carried out, affording the corresponding [5, 6]‐ and [6, 6]‐carbosilylated derivatives. The results of thermal isomerization of these derivatives were in agreement with the calculated relative stabilities. The electronic effect of the silirane addend was confirmed by electrochemical and theoretical studies. More information can be found in the Full Paper by Masahiro Kako, Shigeru Nagase, Takeshi Akasaka et al. onpage 1391 in Issue 12, 2017 (DOI:10.1002/asia.201700506 ).